Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, => 3^x.(1+3+3^2)-1 = 1052
=> 3^x.13 = 1052+1 = 1053
=> 3^x = 1053 : 13
=> 3^x = 81 = 3^4
=> x = 4
b, => x^2-49 >=0 ; 81-x^2 >=0 hoặc x^2-49 < = 0 ; 81-x^2 < = 0
=> 49 < = x^2 < = 81
=> -9 < = x < = -7 hoặc 7 < = x < = 9
=> x thuộc {-9;-8;-7;7;8;9}
Tk mk nha
\(\dfrac{3}{2}\times\dfrac{9}{4}\times\dfrac{81}{16}=\dfrac{3}{2}\times\left(\dfrac{3}{2}\right)^2\times\left(\dfrac{3}{2}\right)^4=\left(\dfrac{3}{2}\right)^7\)
\(\left(\dfrac{1}{2}\right)^7\times8\times32\times2^8=\left(\dfrac{1}{2}\right)^7\times2^3\times2^5\times2^8=\left(\dfrac{1}{7}\right)^7\times2^{16}\)
\(\left(-\dfrac{1}{7}\right)^4\times125\times5=\left(-\dfrac{1}{7}\right)^4\times5^3\times5=\left(-\dfrac{1}{7}\right)^4\times5^4\)
\(4\times32:\left(2^3\times\dfrac{1}{16}\right)=2^2\times2^5:2^3:2^{-4}=2^0\)
\(\left(\dfrac{1}{7}\right)^2\times\dfrac{1}{7}\times49=\left(\dfrac{1}{7}\right)^3\times7^3=1^3\)
6, \(\dfrac{3}{2}\times\dfrac{9}{4}\times\dfrac{81}{16}=\dfrac{3}{2}\times\left(\dfrac{3}{2}\right)^2\times\left(\dfrac{3}{2}\right)^4\)
7,\(\left(\dfrac{1}{2}\right)^7\times8\times32\times2^8=\left(\dfrac{1}{2}\right)^7\times2^3\times2^5\times2^8\)
8,\(\left(-\dfrac{1}{7}\right) ^4\times125\times5=\left(\dfrac{1}{7}\right)^4\times5^3\times5\)
9,\(4\times32:\left(2^3\times\dfrac{1}{16}\right)=2^2\times2^5:\left[2^3\times\left(\dfrac{1}{2}\right)^4\right]\)
10, \(\left(\dfrac{1}{7}\right)^2\times\dfrac{1}{7}\times49=\left(\dfrac{1}{7}\right)^2\times\dfrac{1}{7}\times7^2\)
6:=(3/2)*(3/2)^2*(3/2)^4=(3/2)^7
7: =(1/2)^7*2^3*2^5*2^8=2^9
8: =(-1/7)^4*5^4=(-5/7)^4
9: =2^2*2^5:(2^3/2^4)
=2^7/2=2^6
10: =(1/7)^3*7^2=1/7
a) 3/7 + 4/9 + 4/7 + 5/9
= ( 3/7 + 4/7 ) + ( 4/9 + 5/9 )
= 7/7 + 9/9
= 1 + 1
= 2
b)1/5 + 4/10 + 9/15 + 16/20 + 25/25 + 36/30 + 49/35 + 64/40 + 81/45
= 1/5 + 2/5 + 3/5 + 4/5 + 5/5 + 6/5 + 7/5 + 8/5 + 9/5
= ( 1/5 + 9/5 ) + ( 2/5 + 8/5 ) + (7/5 + 3/5 ) + ( 4/5 + 6/5 ) + 5/5
= 2 + 2 + 2 + 2 + 1
= 2 x 4 + 1
= 8 +1
= 9
c) 1/8 + 1/12 + 3/8 + 5/12
= ( 1/8 + 3/8 ) + ( 1/12 + 5/12)
= 4/8 + 6/12
= 1/2 + 1/2
= 2/4 = 1/2
mỏi tay rồi
d; (1 - \(\dfrac{1}{2}\)) x (1 - \(\dfrac{1}{3}\)) x (1 - \(\dfrac{1}{4}\)) x ... x ( 1 - \(\dfrac{1}{100}\))
= \(\dfrac{1}{2}\) x \(\dfrac{2}{3}\) x \(\dfrac{3}{4}\) x \(\dfrac{3}{4}\) x ... x \(\dfrac{99}{100}\)
= \(\dfrac{1}{100}\)
a) 2x+2x+1+2x+2+2x+3=480
<=> \(2^x+2^x.2+2^x.2^2+2^x.2^3=480\)
<=> \(2^x.\left(1+2+2^2+2^3\right)=480\)
<=>\(2^x=\frac{480}{1+2+2^2+2^3}=32\)
=> x=5
b) (x2-49)*(x2-81)<0 Khi \(\hept{\begin{cases}x^2-49< 0\\x^2-81>0\end{cases}}\) hoặc \(\hept{\begin{cases}x^2-49>0\\x^2-81< 0\end{cases}}\)
TH1 \(\hept{\begin{cases}x^2-49< 0\\x^2-81>0\end{cases}}\)\(\Rightarrow81< x^2< 49\)(Vô lí)
TH2\(\hept{\begin{cases}x^2-49>0\\x^2-81< 0\end{cases}}\) \(\Rightarrow49< x^2< 81\)\(\Leftrightarrow7^2< x^2< 9^2\)Mà x nguyên \(\Rightarrow x=8\)
c) Làm giống câu a
3x : 3 = 81
=> 3x = 81 . 3 = 243 = 35
=> x = 5
22x : 8 = 128
=> 22x = 128 . 8 = 1024 = 210
=> 2x = 10
=> x = 10 : 2
=> x = 5
7x-1 . 49 = 343
7x-1 = 343 : 49 = 7 = 71
=> x - 1 = 1
=> x = 1+1
=> x = 2
\(\left(2x+1\right)^2=49\)
\(\Rightarrow2x+1=7\left(h\right)2x+1=-7\)
\(\Rightarrow2x=6\left(h\right)2x=-8\)
\(\Rightarrow x=3\left(h\right)x=-4\)
\(\left(2x-3\right)^4=81\)
\(\Rightarrow2x-3=3\left(h\right)2x-3=-3\)
\(\Rightarrow2x=6\left(h\right)2x=0\)
\(\Rightarrow x=3\left(h\right)x=0\)